DLR's Mobile Rocket Base - Flight Opportunities for Israeli Universities and Research Institutes - Stamminger, Andreas; Ettl, Josef; Hörschgen-Eggers, Marcus; Jung, Wolfgang; Kimpe, Andreas; Turner, Peter (2015)
The Mobile Rocket Base (MORABA), a departement of DLR’s Space Operations and Astronaut Training Institute fosters the national and international scientific community to prepare and implement sounding rocket and balloon borne experiments in the fields of aeronomy, astronomy, geophysics, hypersonic and especially microgravity research worldwide. In addition, satellite missions can be supported by mobile instrumentation radar for trajectory determination as well as with telemetry, telcommand and command (TT&C) ground stations. MORABA develops and provides mission support for a large number of mechanical and electrical flight systems for use on sounding rockets, balloons and short duration satellite missions. During the last four decades more than 200 campaigns have been performed in the Antarctic, Australia, Brazil, France, Greenland, India, Italy, Japan, Norway, Spain, Sweden and USA. Depending on the scientific aim, an appropriate launch range is selected and complemented or fully equipped with MORABA’s mobile infrastructure, such as launcher, telemetry and tracking stations. Converted surplus military or commercial rocket motors, as well as all necessary mechanical and electrical subsystems are developed and supplied by MORABA. For the launch of rockets, stability and performance calculations are carried out to ensure correct vehicle performance and to meet range safety aspects. This paper will give an overview of MORABA’s infrastructure for sounding rocket missions and it will focus on possible flight opportunities for Israeli universities and research institutes.